Multi-values discrete particle swarm optimization for cross layer resource allocation in cooperative OFDMA systems - Wei LI; Chun-lin XIONG; De-gang WANG; Xiao-ying ZHANG; Ji-bo WEI (Tongxin xuebao, 2014)
The resource allocation problem in cooperative OFDMA systems with mobile stations (MS) on multi-services was investigated. In order to maximize the sum utility of all MS under per-relay power constraint(PPC), an asymptotic optimal resource allocation algorithm based on multi-values discrete particle swarm optimization (MDPSO) was pro-posed. Unlike the traditional discrete particle swarm optimization (DPSO) algorithm, the proposed one denotes the parti-cle position by discrete multi-value variable. Furthermore, new probability based operations for computing particle veloc-ity and updating particle positions were developed, and the mutation of particle positions was also introduced to over-come the premature convergence problem. The proposed MDPSO can also be applied widely to solve the combinatorial optimization problems (COP). Furthermore, iterative waterfilling was used to complete power allocation. Simulation re-sults show that the proposed method achieves higher sum utility of all MSs and higher degree of user fairness than the existing methods.